False, since it we substitute x = 4 into the equation we get y = -4 + 3 = -1
Answer:
Below
Step-by-step explanation:
First we can go ahead and create a general equation for this polynomial
Here are our roots :
x1 = - 3
x2 = -1
x3 = 1
Now because this function extends from quadrant 4 to 3, we know that this has been reflected in the x-axis :
f(x) = - ( x + 3 ) ( x + 1 ) ( x - 1 )
However if we look closely you can see that the graph appears to "bounce" off certain roots. In this case it bounces off x = 1. This means that this root is an order of 2. It also has a weird looking curve on x = - 3 which means that this root is an order of 3.
Our general equation will look like this :
f(x) = - ( x + 3 )^3 ( x - 1 )^2 ( x + 1 )
Now we need to sub in any point on the graph to solve for the <em>a </em>value. I'm just going to arbitrarily pick the y-intercept at ( 0 , -3 )
- 3 = - a ( 0 + 3 )^3 ( 0 - 1 )^2 ( 0 + 1 )
- 3 = - a (3)^3 (-1)^2 (1)
- 3 = - a (27)(1)(1)
- 3 = - a27
1/9 = a
Here is our FINAL equation :
f(x) = - 1/9 ( x + 3 )^3 ( x - 1 )^2 ( x + 1 )
Hope this helps! Best of luck <3
I would really appreciate a brainliest if possible :)
Answer:
2/2
Step-by-step explanation:
Answer:
10859.94
Step-by-step explanation:
To solve this, you need to know the formula for solving the area of a circle: πr²
The first thing you should do is find the area of the square: 78 x 78 = 6084
Then, we find the area of the circle. To do this, we must figure out the radius. Luckily, the problem states that the combined diameter of both half circles is 78, which means the radius is 39. Then, we can apply the formula: π39².
39² = 1521
1521 x 3.14 = 4775.94
This is the combined area of both half circles.
Finally, we have to add: 4775.94 + 6084 = 10859.94